Moral and Ethic:: A Psychological Reading - La Taille, Yves de (2010)
After nearly a century of reflections and investigations, as it would be expected, the classical theoretical referentials of Moral Psychology show signs of exhaustion. Consequently, new perspectives open up, including the theoretical approach that takes the name of ‘ethic personality’, whose thesis is: to understand the moral behavior (duties) of individuals, one needs to know the ethical perspective (good life) adopted by them. Among the psychological invariants to hold a ‘good life’ is the need for ‘expansion of the self’. Such expansion involves positive ‘self representations’, among of which may be those related to morality. If so, the subject will experience the feeling of duty, otherwise, the motivation for moral action will be weak or non-existent.